Revealing Equiterra Campaign by United Nations Women: Multimodal Perspective - Mira Melati Sukma; Laily Maulida Septiana Harti; Lisetyo Ariyanti (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2022)
Equiterra is a digital campaign that was released on 2020 International Women's Day by United Nations Women and Ruby Taylor. It is a digital illustration of a utopian country where equality and fairness manifested. It is constructed by rich verbal and visual elements which makes it a multimodal text. This study aims to analyze the three metafunctions of visual and verbal elements of Equiterra. The study is conducted using a qualitative method by analyzing the visual and verbal elements within illustration using the theory of Systemic Functional Linguistics by Halliday and Matthiessen (2014) and Visual Grammar by Kress and van Leeuwen (2006), also analyzing the interplay between verbal and visual elements using Intersemiotic Complementarity by Royce (1998). The data are the nine parts of Equiterra which are taken from the official website of United Nations Women that are separated but also joined together into forming a path. The analysis finds that Equiterra tries to represent people with various socio-cultural backgrounds to perform their activities and to obtain their maximum potential fairly and equally along with actively encouraging the viewer to make it possible. Furthermore, Equiterra is a feminist digital media that delivers the intersectional issues related to gender, equality, and inclusion which are used to raise awareness towards the problems around these topics.